2020
DOI: 10.1111/pde.14069
|View full text |Cite
|
Sign up to set email alerts
|

Acquired syphilis in children: A retrospective study over two‐and‐a‐half decades in a tertiary care center in northern India

Abstract: Background Syphilis causes considerable morbidity not only in adults but also in children. Unfortunately, acquired syphilis in children has not received due attention and remains a relatively ignored field. Methods This was a retrospective study, in which epidemiologic, clinical, and investigational data were analyzed from medical records of all sexually transmitted infection (STI) cases attending the STI clinic of Pt. B. D. Sharma, PGIMS, Rohtak from January 1992 to November 2018. Children of age ≤14 years wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…3 Sexual abuse is also another consideration for children with syphilis. 4 Acquired syphilis by nonsexual contact is very rare in the postantibiotic era, although it was common in the early 1900s. 5…”
Section: Denouementmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Sexual abuse is also another consideration for children with syphilis. 4 Acquired syphilis by nonsexual contact is very rare in the postantibiotic era, although it was common in the early 1900s. 5…”
Section: Denouementmentioning
confidence: 99%
“…8 In the postantibiotic era, there are few case reports in the medical literature regarding nonsexual syphilis transmission in children, and most were associated with feeding children premasticated foods. 4,9 Moscatelli et al 9 from Argentina recently published the first nonsexually acquired syphilis study in the 21st century. In their retrospective study, they reported 24 patients with nonsexually acquired syphilis with a median age of 4.2 years and the youngest and the oldest being 1 and 17 years of age, respectively.…”
Section: Denouementmentioning
confidence: 99%
See 1 more Smart Citation